In Vitro Models for Studying Respiratory Host–Pathogen Interactions. Issue 6 (4th May 2021) - Barron, Sarah L.; Saez, Janire; Owens, Róisín M.
Abstract: Respiratory diseases and lower respiratory tract infections are among the leading cause of death worldwide and, especially given the recent severe acute respiratory syndrome coronavirus‐2 pandemic, are of high and prevalent socio‐economic importance. In vitro models, which accurately represent the lung microenvironment, are of increasing significance given the ethical concerns around animal work and the lack of translation to human disease, as well as the lengthy time to market and the attrition rates associated with clinical trials. This review gives an overview of the biological and immunological components involved in regulating the respiratory epithelium system in health, disease, and infection. The evolution from 2D to 3D cell biology and to more advanced technological integrated models for studying respiratory host–pathogen interactions are reviewed and provide a reference point for understanding the in vitro modeling requirements. Finally, the current limitations and future perspectives for advancing this field are presented. Abstract : Respiratory diseases and infection are leading causes of death. This review gives a primer on biological, immunological, and pathological components occurring during respiratory infection in health and disease and provides a reference point for understanding in vitro modeling requirements. Finally, an overview of 2D, 3D, and advanced technological models are given, with prospects for the future of this field.